Evolucion del contenido en hidrocarburos y azucares en Euphorbia lathyris L. - Pelacho, A.M.=700 1 Mingo-Castel, A.M.
(Es, En)
ilus., 6 ref.
Keywords: EUPHORBIA LATHYRIS; METABOLISMO; AGRICULTURA; ENERGIA; HIDROCARBUROS; AZUCARES; LATEX; VERNALIZACION; ESPAÑA